2016
DOI: 10.7554/elife.20609
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional secretory processing diversifies neuronal ion channel properties

Abstract: N-glycosylation – the sequential addition of complex sugars to adhesion proteins, neurotransmitter receptors, ion channels and secreted trophic factors as they progress through the endoplasmic reticulum and the Golgi apparatus – is one of the most frequent protein modifications. In mammals, most organ-specific N-glycosylation events occur in the brain. Yet, little is known about the nature, function and regulation of N-glycosylation in neurons. Using imaging, quantitative immunoblotting and mass spectrometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
121
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 68 publications
13
121
0
1
Order By: Relevance
“…We note, however, that it has recently been reported that KARs with an immature glycosylation state accumulate at the cell surface, suggesting that not all KARs are processed within the Golgi (Hanus et al., 2016). Like long-term regulation of iGluR synthesis by transcription and translation and short-term regulation by endocytosis and recycling of surface-expressed iGluRs, the intermediate-term processes of trafficking through the secretory pathway are also under tight activity-dependent control.…”
Section: Discussionmentioning
confidence: 58%
“…We note, however, that it has recently been reported that KARs with an immature glycosylation state accumulate at the cell surface, suggesting that not all KARs are processed within the Golgi (Hanus et al., 2016). Like long-term regulation of iGluR synthesis by transcription and translation and short-term regulation by endocytosis and recycling of surface-expressed iGluRs, the intermediate-term processes of trafficking through the secretory pathway are also under tight activity-dependent control.…”
Section: Discussionmentioning
confidence: 58%
“…The precise glycan composition of oligosaccharide chains conjugated to iGluRs is not clear, although functional surface receptors carry both high‐mannose and complex glycans (Hanus et al . ; Kaniakova et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Neurons have more immature/core N-glycan structures on the cell surface, suggesting that N-glycosylation does not follow the intricate process that results in the complex sugar structures observed in other cell types (Hanus et al 2016) (Fig. 2).…”
Section: Golgi Trafficking and Glycosylation In Neuronsmentioning
confidence: 99%
“…2). Hanus et al (2016) speculate that proteins with immature N-glycans bypass the Golgi as Golgi disassembly had no effect on PM distribution of these proteins (Hanus et al 2016). Via an unidentified sorting process, proteins could exit the ER/cis-Golgi, without completely traversing the Golgi, and produce fully functional receptors (Hanus et al 2016; Jeyifous et al 2009).…”
Section: Golgi Trafficking and Glycosylation In Neuronsmentioning
confidence: 99%
See 1 more Smart Citation